Factors associated with compassion fatigue and compassion satisfaction in obstetrics and gynaecology nurses: A cross‐sectional study - Jia Wang; Mei Su; Wenzhong Chang; Yuchong Hu; Yujia Ma; Peijuan Tang; Jiaxin Sun (Wiley, 2023)
Abstract Aims To examine the factors influencing compassion fatigue and compassion satisfaction in obstetrics and gynaecology nurses and to explore the combined results of multiple factors. Design An online cross‐sectional study was conducted. Review Methods Data were collected from 311 nurses using a convenience sampling method from January to February 2022. Stepwise multiple linear regression analysis and mediation tests were performed. Results Compassion fatigue in obstetrics and gynaecology nurses was in the moderate to high levels. Physical status, number of children, emotional labour, lack of professional efficacy, emotional exhaustion and the none‐only‐child can influence compassion fatigue; lack of professional efficacy, cynicism, social support, work experience, employment status and night shift were predictive of compassion satisfaction. Social support partially mediated between lack of professional efficacy and compassion fatigue/compassion satisfaction; emotional labour moderated in the mediated analysis model. Conclusion Moderate to high levels of compassion fatigue was present in 75.88% of obstetrics and gynaecology nurses. Some factors affect compassion fatigue and compassion satisfaction. Thus, nursing managers should consider factors and construct a monitoring system to reduce compassion fatigue and improve compassion satisfaction. Implications for the Profession The results will provide a theoretical basis for improving job satisfaction and the quality of care in obstetrics and gynaecology nurses. And this may raise concerns about the occupational health of obstetrics and gynaecology nurses in China. Reporting Method The study was reported according to the STROBE. Patient or Public Contribution The nurses spent time filling out the questionnaires during the data collection phase and answered the questions sincerely. What does this article contribute to the wider global clinical community? Obstetrics and gynaecology nurses with 4-16 years of experience are prone to experience compassion fatigue. The effect of lack of professional efficacy on compassion fatigue and compassion satisfaction can be improved by social support. Relevance to Clinical Practice Reducing nurse compassion fatigue and improving compassion satisfaction are important for providing quality nursing care to obstetrics and gynaecology patients. In addition, clarifying the influencing factors of compassion fatigue and compassion satisfaction can improve nurses' work efficiency and job satisfaction, and provide theoretical guidance for managers to implement interventions.